2019
DOI: 10.1002/jcb.29306
|View full text |Cite
|
Sign up to set email alerts
|

ssc‐miR‐204 regulates porcine preadipocyte differentiation and apoptosis by targeting TGFBR1 and TGFBR2

Abstract: MicroRNAs (miRNAs) take part in a variety of biological processes by regulating target genes. Transforming growth factor β receptor 1 (TGFBR1) and TGFBR2 are crucial members of the TGF‐β family and are serine/threonine kinase receptors. The aim of this study was to explore the functions of ssc‐miR‐204 in porcine preadipocyte differentiation and apoptosis with regard to the TGFβ/Smad pathway. We identified miRNAs predicted to target TGFBR1 and TGFBR2 using a database and selected ssc‐miR‐204 as a candidate miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Based on the above results, SMAD4 functions mostly as a positive regulator of cell proliferation. Moreover, the SMAD4 and TGF-β signaling pathways play important roles in miRNA regulation of cell proliferation [41,42]. Notably, miR-183 promotes preadipocyte adipogenesis by suppressing SMAD4 expression in goats [43], and myostatin/ SMAD4 signaling inhibits 3T3-L1 cell differentiation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above results, SMAD4 functions mostly as a positive regulator of cell proliferation. Moreover, the SMAD4 and TGF-β signaling pathways play important roles in miRNA regulation of cell proliferation [41,42]. Notably, miR-183 promotes preadipocyte adipogenesis by suppressing SMAD4 expression in goats [43], and myostatin/ SMAD4 signaling inhibits 3T3-L1 cell differentiation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Based on above results, SMAD4 is mostly a positive regulator of cell proliferation. Moreover, The SMAD4 and TGF-β signaling pathways played important roles in the process of miRNA regulating cell proliferation, respectively [36,37]. Here, we revealed that miR-146a-5p targeting the SMAD4 was identi ed as a novel miRNA that repressed proliferation of porcine intramuscular preadipocytes via the TGF-β signaling pathway.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings revealed that the highly expressed DEmiRNA miR-204 exhibited the most significant expression alteration subsequent to gut microbiota depletion. Previous studies have reported that miR-204 regulates the differentiation of mammalian preadipocytes, thereby influencing fat deposition ( Jin et al, 2019 ; Zhang et al, 2020 ). These results suggest that miR-204 may be a crucial target of gut microbiota in regulating the lipogenesis of chickens.…”
Section: Discussionmentioning
confidence: 99%